2011
DOI: 10.1002/chem.201002825
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Detection of DNA by Modulation of Thrombin Activity on Gold Nanoparticles

Abstract: A colorimetric, non-cross-linking aggregation-based gold-nanoparticle (AuNP) probe has been developed for the detection of DNA and the analysis of single-nucleotide polymorphism (SNP). The probe acts by modulating the enzyme activity of thrombin relative to fibrinogen. A thrombin-binding aptamer with a 29-base-long oligonucleotide (TBA(29)) assembled on the nanoparticles (TBA(29)-AuNPs) through sandwich DNA hybridization was found to possess ultra-high anticoagulant potency. The enzyme inhibition of thrombin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Jian and Huang [131] reported a colorimetric detection of DNA sequences using a non-cross-linking approach. They found that the spatial distance between AuNP and thrombin (i.e., a serine protease involved in a multitude of biological processes) has a strong influence on the catalytic activity of thrombin.…”
Section: Dna Determinationmentioning
confidence: 99%
“…Jian and Huang [131] reported a colorimetric detection of DNA sequences using a non-cross-linking approach. They found that the spatial distance between AuNP and thrombin (i.e., a serine protease involved in a multitude of biological processes) has a strong influence on the catalytic activity of thrombin.…”
Section: Dna Determinationmentioning
confidence: 99%
“…A second pool of Au-nps modified with thrombin substrate fibrinogen was not converted into aggregated fibrin-Au-nps due to binding of fully complementary DNA to the former Au-nps. This assay allowed detection of DNA by the naked eye at 12 pM concentration, although no information of the type of mismatch could be gained by this method [51]. Finally, a product of an SNP containing gene can also be applied for SNP sensing [52].…”
Section: Nucleic Acid Aptamers and Proteins In Snp Diagnosticsmentioning
confidence: 99%
“…A colorimetric detection assay was reported using cross-linking [48] or non-cross-linking of Au-nps mediated by DNA aptamers [49]. Among other DNA aptamers, a 29-nt long thrombin-binding aptamer (TBA) has been well studied and already applied in SNP diagnostics [50,51]. Chen and co-workers used self-assembled bivalent thrombin-binding aptamers and fibrinogen-conjugated Au-nps to detect DNA, based on controlled thrombin activity ( Figure 4C) [50].…”
Section: Nucleic Acid Aptamers and Proteins In Snp Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations